Beaver (Castor fiber) Activity in an Archaeological Context: A Mid-Holocene Beaver Burrow Feature and a Late-Holocene Ecofact at the Late Palaeolithic Grabow Site, Northern Germany*. Issue 1 (1st January 2017) - Tolksdorf, Johann Friedrich; Turner, Falko; Veil, Stephan; Bittmann, Felix; Breest, Klaus
ABSTRACT: Bioturbation and intrusive ecofacts are major concerns for the analysis of archaeological sites in wetland environments. Post-sedimentary influence of beavers ( Castor fiber ) is described for a well dated Late Palaeolithic archaeological record situated in a floodplain in Northern Germany. An extensive burrow system was documented and analysed according to its spatial dimensions and sedimentological properties; it was interpreted to be the result of beaver activity. Palynological analyses proved a Mid-Holocene origin of the infill material and helped in understanding the history of site formation. In addition, a pointed piece of wood was examined and identified as ecofact, which had been gnawed by a small rodent, possibly Arvicola amphibius (water vole). Our study thus illustrates the potential complexity of post-sedimentary site-alteration, describes the sub-surface morphology of a burrow system in a wetland context and documents risks for erroneous archaeological interpretation.